IN HOUSE TRAINING PEMBELAJARAN STEM BERBASIS ENGINEERING DESIGN PROCESS KEPADA GURU SMK DARUL MUQOMAH KABUPATEN JEMBER - Handayani, Rif’ati Dina; Dewi, Nila Mutia; Lesmono, Albertus Djoko; Supriadi, Bambang; Maryani, Maryani (LPPM Universitas Flores, 2024)
In the era of the Industrial Revolution 4.0, people are required to have skills, knowledge, and abilities in various fields. Therefore, integrating 21st-century skills into the learning process is very important. Learning should emphasise critical thinking, creativity and innovation, collaboration, and communication. One method that can be used to enhance 21st-century skills is STEM learning based on the engineering design process. This community service activity was carried out over three months and was divided into four phases: the preparation phase, the planning phase, the implementation phase, and the evaluation phase. The results of the activity show that the majority of teachers at SMK Darul Muqomah have a good understanding of STEM learning based on the engineering design process. Overall, this training has been well executed. The participants stated that the training was beneficial and could expand their understanding of STEM learning based on the engineering design process. Specifically, this training provided an overview of the application of the STEM approach in school learning. All participants showed interest and willingness to implement STEM learning in their classes. However, it is important to note the challenges or obstacles in implementing the STEM approach in the classroom.